Women Cardiovascular Awareness And Physical Activity Promotion - Muliantino, Mulyanti Roberto; Ananda, Yuanita; Afriyanti, Esi; Merdawati, Leni; Mailani, Fitri; Muthia, Rahmi; Rahayu, Siski (Warta Pengabdian Andalas, 2026)
Women's insufficient cardiovascular awareness remains a major obstacle in preventing cardiovascular disease (CVD) within this demographic. Addressing key contributing elements such as inactive lifestyles and insufficient physical activity among females is essential. The SEJIWA group, a women's fitness team in Padang, aims to foster healthy living, consistent physical training, and advancement in cardiac wellness. This program seeks to strengthen cardiovascular awareness and establish routine exercise culture among SEJIWA members. Various techniques were employed, encompassing educational sessions, promotional activities, health assessments, and practical training. The program ran from July through August 2025, with participation from 30 female SEJIWA members. Results revealed enhanced cardiac awareness score following education (50.04 versus 69.80), elevated physical activity measurements after weekly exercise routines (642.56 versus 940.38 MET). The majority exhibited unhealthy waist measurements, most participants were either obese or overweight, over half demonstrated elevated blood pressure readings and hypertension, most showed high cholesterol levels, while only a minority presented with elevated blood glucose. This program illustrated the efficacy of combined interventions including education, promotional strategies, screening, and consistent exercise in enhancing awareness and behavioral patterns. Nevertheless, the substantial CVD risk factors observed among participants highlight the critical need for sustained programs targeting CVD prevention in women.